Chemical toxicity and radioactivity of depleted uranium: The evidence from in vivo and in vitro studies - Asic, Adna; Kurtovic-Kozaric, Amina; Besic, Larisa; Mehinovic, Lejla; Hasic, Azra; Kozaric, Mirza; Hukic, Mirsada; Marjanovic, Damir (Environmental research, 2017)
The main aim of this review is to summarize and discuss the current state of knowledge on chemical toxicity and radioactivity of depleted uranium (DU) and their effect on living systems and cell lines. This was done by presenting a summary of previous investigations conducted on different mammalian body systems and cell cultures in terms of potential changes caused by either chemical toxicity or radioactivity of DU. In addition, the authors aimed to point out the limitations of those studies and possible future directions. The majority of both in vitro and in vivo studies performed using animal models regarding possible effects caused by acute or chronic DU exposure has been reviewed. Furthermore, exposure time and dose, DU particle solubility, and uranium isotopes as factors affecting the extent of DU effects have been discussed. Special attention has been dedicated to chromosomal aberrations, DNA damage and DNA breaks, as well as micronuclei formation and epigenetic changes, as DU has recently been considered a possible causative factor of all these processes. Therefore, this approach might represent a novel area of study of DU-related irradiation effects on health. Since different studies offer contradictory results, the main aim of this review is to summarize and briefly discuss previously obtained results in order to identify the current opinion on DU toxicity and radioactivity effects in relation to exposure type and duration, as well as DU properties. •Uranium is an actinide heavy metal that is chemically toxic and radioactive.•Depleted uranium (DU) has a lower fraction of 235U isotope when compared to natural U.•In vivo and in vitro studies were assessing the influence of DU irradiation.•DU is inducing epigenetic changes in mice and fish.•DU released in the environment is a serious pollutant and toxic to the living organisms.